Histopathological Spectrum of Renal Tumors in Adults in Nephrectomy Specimens in a Tertiary Care Center - Sharma, Nisha; Maharjan, Daisy (Journal of Institute of Medicine Nepal, 2022)
Introduction Renal neoplasms are heterogeneous tumors with clinical picture, prognosis and therapeutic implications differing with the various histological subtypes. There are limited studies on adult renal tumors conducted in Nepal so far. This study aims to provide a better assessment on the histopathological spectrum of renal neoplasms in adult population. Methods This is a descriptive study of all the nephrectomy specimens of adults received at Department of Pathology, Tribhuvan University Teaching Hospital from January 2013 to January 2020. Results There were 75 males and 35 females with mean age being 51.8 years. Malignant tumors (99 cases, 90%) were more common than benign tumors (11 cases, 10%). Renal cell carcinoma (RCC) was the most common malignant tumor consisting of 91 cases (82.72%) followed by 6 cases of urothelial carcinoma (5.45%) and 2 cases of primitive neuroectodermal tumor. (PNET) (1.8%). Clear cell RCC (78 cases, 70.90%) was the commonest histological subtype of RCC followed by papillary RCC (8 cases, 7.2%) and chromophobe RCC (2cases, 1.8%). 42.65% of the cases of clear cell RCC were of WHO/ISUP grade 2, whereas, most of the cases of papillary RCC were of low grade (Grade 1, 37.5%). Majority of Renal cell carcinomas were in stage pT1a (28 cases, 34.56%). Conclusion Clear cell RCC was the most common renal tumor in adults comprising the majority of cases. These tumors mostly demonstrated WHO/ISUP Nuclear grade 2 and early stage of presentation (pT1). Papillary RCC was the second commonest RCC and mostly presented at lower nuclear grade (WHO/ISUP Nuclear grade 1). Urothelial carcinomas demonstrated higher nuclear grade and stage compared with RCC.